Development of Physics Electronic Modules Using the Trait–Treatment Interaction Model Based on Next Generation Science Standards - Putri, Rahmi Tania; Aswirna, Prima; Asrar, Allan (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to develop a physics electronic module using the Trait Treatment Interaction (TTI) model based on the Next Generation Science Standards (NGSS) to improve students' ability to Construct Explanations and Design Solutions (CEDs) and to test its effectiveness on the topic of Environmental Pollution for grade X SMA/MA. The study uses a Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The Define stage includes front-end, student, task, and concept analysis, while the Design stage involves preparing instruments and selecting media. The Develop stage consists of validation by content, media, and language experts, followed by product trials with educators and students, and the Disseminate stage focuses on distributing the effective product. The research subjects were 34 students of class X.I MAN 2 Pesisir Selatan. The findings show that the developed e-module is of very high quality and highly valid, with an average score of 89.24% from expert validators, while its practicality level reached 88.97% based on evaluations from educators and students. The e-module also proved very effective in improving students’ CEDs abilities, indicated by an average test score of 90%. High-ability students (faster learners) experienced significant improvement through self-learning, whereas low-ability students (slower learners) benefited more from regular teaching accompanied by additional tutorials. Based on these results, it is recommended that the e-module be further developed for other physics topics, and future researchers are encouraged to optimize time efficiency to ensure a smoother learning process without disrupting the predetermined duration.